FIELD-BASED ASSESSMENT OF GENETIC DIVERSITY AND YIELD CHARACTERS IN EXOTIC KABULI CHICKPEA (CICER ARIETINUM L.) GERMPLASM UNDER NORMAL AND WATER DEFICIT CONDITIONS - REHMAN , MU; MAJEED , HN; MOON , A; ZAFAR , MM; BATOOL , R; AHSAN , M; IQBAL, A (Biological and Clinical Sciences Research Journal, 2024)
Drought stress is a major factor that affects chickpea production, especially in dry areas of the world. This study assessed the genetic variation of one hundred Kabuli chickpea germplasm accessions from the International Center for Agricultural Research in the dry areas under control and stress conditions. The study was done at the University of Agriculture Faisalabad, in the Department of Plant Breeding and Genetics. Using analysis of variance (ANOVA), it was established that genotypes in the two environments, that is, controlled and water-deficit environments differed significantly. Thirty-seven genotypes offered higher standard checks under water stress in addition to 61 under normal growing disorders. Regression analysis revealed that plant height had a significantly positive effect on biological yield (r=0.376**), pods per plant (r=0.251*), hundred-seed weight (r=0.278**) and yield per plot (r=0.339**). Plot yield was significantly related to seed yield at r = 1.000**. The scatter biplot analysis revealed that 14 genotypes (22225, 22228, 22219, 22274, 22267, 22256, 22266, 22264, 2204, 22276, 22271, 22236, 22215, 22277) were significantly less sensitive to drought stress as they were distinctly clustered away from other genotypes in the plot. High variability was observed in traits such as hundred-seed weight, harvest index, and biological yield. The results indicate a high level of genetic variation in the chickpea germplasm that can be utilized to develop improved drought-tolerant chickpea varieties with enhanced yield potential.